Acute Stroke in Middle Cerebellar Peduncle in a Patient With FXTAS - Hall, Deborah A.; Fraint, Avram; Dafer, Rima (Frontiers in Genetics, 2018)
Background: Fragile-X associated tremor/ataxia syndrome (FXTAS) is commonly associated with T2 hyperintensity in the middle cerebellar peduncles (MCP) on MRI. However ischemic stroke in the MCP in a patient with FXTAS has not previously been described. Case Description: A 61-year-old man with hypertension, sleep apnea, obesity, and FXTAS presented to the emergency department with two days of worsening balance and nausea which began two days after chiropractic neck manipulation. Examination revealed new nystagmus and worsening dysmetria. Workup revealed an acute infarct in the left MCP, atherosclerotic narrowing of the V4 segment of the left vertebral artery, inadequately controlled hypertension, and a LDL of 127. Conclusions: Isolated MCP infarcts are rare and typically associated with hypoperfusion in the setting of vertebral artery disease and neck manipulation. We suspect that underlying neurodegeneration due to FXTAS with superimposed small vessel disease and neck manipulation may have caused preferential damage to the Purkinje cells in the MCP.